Niepolityczna szopka polityczna. (Gdynia : [s.n.], 1946)
Afisz inf. o szopce autorstwa S. Fleszarowej.
Keywords: Fleszarowa-Muskat, Stanisława -- (1919-1989).; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- życie artystyczne